Modulation of the Endocannabinoid System via Inhibition of Fatty Acid Amide Hydrolase (FAAH) by Novel Urea and Carbamate Derivatives. Issue 39 (22nd October 2019) - Cramer, Sarah; Johnson, Jacklyn; Ngo, Thanh; El‐Alfy, Abir T.; Stec, Jozef
Abstract: Recent discoveries in the physiology and pharmacology of the endocannabinoid system (ECS) ushered in new therapeutic potential for the treatment of pain, inflammatory, sleep, eating, and various CNS disorders. To date, diverse synthetic molecules have been reported to target the cannabinoid (CB) receptors. While very potent, the exogenous agonists of CB receptors are often accompanied by adverse effects such as impaired memory, cognition, and most notably addiction. On the contrary, the known endogenous agonists such as anandamide (AEA) and 2‐arachidonoylglycerol (2‐AG) are susceptible to enzyme‐mediated hydrolysis thus are not feasible as therapeutic agents. Fatty acid amide hydrolase (FAAH) is the principal enzyme responsible for degradation of anandamide and related regulatory lipophilic molecules such as oleamide. Inhibition of FAAH potentiates the action of the endogenous CB agonists, thus provides an indirect approach to modulate the endocannabinoid system. This approach also eliminates the unwanted adverse effects observed with the use of direct synthetic CB agonists. An efficient one‐pot, two‐step synthetic protocol was used to prepare a focused library of lipophilic compounds with potential inhibitory activity of FAAH. Those molecules were screened in vitro and their activity was reported as percent (%) of enzyme's inhibition. Overall, several analogs showed 40% or greater inhibition of FAAH at 100 μM compound's concentration, and many of them also retained high activity at 50 μM compound's concentration. Those results imply that diacyl ureas, acyl ureas and acyl carbamates can serve as the starting point for medicinal chemistry structure optimization in search of novel inhibitors of FAAH. Abstract : Fatty acid amide hydrolase (FAAH) is a key enzyme operating within the endocannabinoid system (ECS). Inhibition of FAAH results in an indirect yet viable approach to modulation of the ECS. Herein we showcase novel diacyl urea compound 4 f (Table 1, entry 6) that inhibited FAAH to the extent of 70% whereas the acyl carbamates 8 a and 8 n (Table 1, entry 21 and 34, respectively) inhibited the enzyme to the extent of 69% at 100 μM concentration and thus they show potential for further drug development. Abbreviations: AA – arachidonic acid, AEA – arachidonoylethanolamide (anandamide), CB – cannabinoid receptor, CM – cytoplasmic membrane, ETA – ethanolamine.